The Role of Selenium in Ameliorating Heat Stress on Thermoregulatory, Growth and Haematological Indices of Broiler Chickens - Ndubuisi, D.I.; Abdulrashid, M.; Daudu, O.M. (Nigerian Journal of Animal Science and Technology (NJAST), 2021)
The study was conducted to evaluate the role of selenium in ameliorating the impact of heat stress on physiological and growth performance of broiler chickens. Two hundred and fifty six, Cobb 500 broiler chickens were used for this experiment; they were randomly distributed into four experimental treatments with selenium supplementation at 0, 0.1, 0.2 and 0.3 mg/kg with four replicates in a Completely Randomized Design. The study comprised the starter (1-28 days) and finisher (28-49 day) phase. Thermoregulatory parameters were similar (p>0.05) with increase in selenium supplementation. At the starter phase, daily feed intake, daily weight gain, final weight, feed conversion ratio and mortality were similar (p>0.05). Birds fed the diet supplemented with 0.2 mgSe/kg had an increase (p<0.05) in daily water intake (149.86). At the finisher phase, all the parameters measured were similar (p>0.05). At the end of the starter phase, most haematological indices were similar (p>0.05) but higher (p<0.05) band cell count was observed for birds fed 0.2 and 0.3 mgSe/kg. At the end of the finisher phase, an increase (P<0.05) in packed cell volume (33.88), haemoglobin (11.28) and erythrocytes (5.50) was observed at 0.1 mgSe/kg supplementation. In conclusion 0.3 mg of selenium supplementation in the feed of broiler chickens had no detrimental effect on performance of broiler chickens and had the least feed cost per kg gain.